The Ties of Place: Contractors and Employer Strategies on the Western Canadian and Central Queensland Coalfields - Bowden, Bradley (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2004)
This study explores the ways in which spatial configurations have shaped the use of contractors in the export coalfields of Queensland (Australia) and western Canada since the late 1960s. It is argued that the divergent employer strategies pursued after 1996—whereby Queensland producers dramatically increased their use of contractors while their Canadian counterparts did not—reflects their different spatial placement within the global coal trade. In Canada, the main problem was locational disadvantage due to distance from deep-water. In consequence, employers responded to falling prices by concentrating production in the area of greatest locational advantage. For Queensland producers, the issue was high mine-site labour costs. In this context, using contractors was part of a strategy to transform labour relations through the Workplace Relations Act.